2002
DOI: 10.1128/mcb.22.20.7337-7350.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of E47-Pip Interaction on DNA Resulting in Transcriptional Synergy and Activation of Immunoglobulin Germ Line Sterile Transcripts

Abstract: E47 and Pip are proteins crucial for proper B-cell development. E47 and Pip cooperatively bind to adjacent sites in the immunoglobulin kappa chain 3 enhancer and generate a potent transcriptional synergy. We generated protein-DNA computer models to visualize E47 and Pip bound to DNA. These models predict precise interactions between the two proteins. We tested predictions deduced from these models by mutagenesis studies and found evidence for novel direct interactions between the E47 helix-loop-helix domain (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…IRF-4 requires an interaction partner, such as PU.1, to efficiently bind DNA and activate transcription (63). It has recently been shown that E47 can bind to DNA cooperatively with IRF-4 to synergistically activate transcription of Ig germline transcription (64). Therefore it is possible that these types of transcription factor interactions could compensate for the loss of PU.1 and/or Spi-B activity.…”
Section: Discussionmentioning
confidence: 99%
“…IRF-4 requires an interaction partner, such as PU.1, to efficiently bind DNA and activate transcription (63). It has recently been shown that E47 can bind to DNA cooperatively with IRF-4 to synergistically activate transcription of Ig germline transcription (64). Therefore it is possible that these types of transcription factor interactions could compensate for the loss of PU.1 and/or Spi-B activity.…”
Section: Discussionmentioning
confidence: 99%
“…5D), because IRF-8 has recently been reported to participate in the activation of AID gene expression (15). It is also interesting that anti-IgM reduced the expression of IRF-4 mRNA, because IRF-4 has been shown to synergize with the E2A protein E47 at another promoter, the I promoter activating germ line I transcription, which is required for isotype class switching (28,29). In addition, IRF4-deficient B cells have been shown to display impaired expression of AID and lack class-switch recombination (30).…”
Section: Discussionmentioning
confidence: 99%
“…IRF4 and Spi-B, when expressed in Abelson transformed pro-B cells, are sufficient to activate germline transcription (18). IRF4,8 have been found to interact with the E2A family of transcription factors to regulate activities of both Ig H chain intron enhancer and 3Ј enhancer (19,20). It has been shown that the interaction of IRF4 and E2A enhances binding affinity of E2A for the E3Ј enhancer.…”
mentioning
confidence: 99%